Aggressive NK cell leukemia. Presentation of a case - Tello-Vera, Stalin; Carpio-Vásquez, Wendy Del Carmen; Chira-Sosa, Jorge; Becerra-Gutiérrez, Lizzie Karen (Acta Biomedica Atenei Parmensis, 2026)
Aggressive natural killer (NK) cell leukemia, is a systemic neoplastic proliferation, usually associated with Epstein-Barr Virus and aggressive clinical course. The objective was characterize a case of aggressive NK cell leukemia and the usefulness of flow cytometry. A 29-year-old woman with a history of Systemic lupus erythematosus (SLE). One month before her admission, she started with abdominal pain predominantly in the epigastrium and left upper quadrant, received two pulses of methylprednisolone. Five days before admission he presented unquantified thermal rise so he went to the hospital, She was admitted to the emergency department of the Almanzor Aguinaga Asenjo Hospital in Chiclayo, Peru.  Reporting on admission appears to be in generally good condition (GGC), apparent normal nutritional status (NNS), apparent normal level of hydration (NH), ventilating spontaneously, oral cavity with lesions, presence of purpuric petechiae in anterior trunk and abdomen, rhythmic heart sounds, capillary filling